Prevalence of Substance Abuse and Its Impact on Senior Citizens in Jalingo Local Government Area, Taraba State, Nigeria - Nathaniel, Noel Anthony; Maikomo, John Moses (International Journal of Humanities, Education, and Social Sciences, 2024)
In recent years, drug abuse has been a major source of concern in Nigeria and other part of the globe. This concern is associated is associated with the enormous effect potency of drug abuse on perpetrators. The above scenario stimulated the researchers to examine the prevalence and impact of drug abuse among senior citizens in Jalingo, Taraba State, Nigeria. The study was anchored on the social learning theory and survey research design was adopted. The population of the study comprised of senior citizens in Jalingo, Taraba State. Findings of the study unraveled that there is a prevalence of drug abuse among senior citizens in Jalingo. Furthermore, it was also found that alcohol is the most commonly abused substance among senior citizens in Jalingo. Based on the revelation, the study recommend among other things the need for consistent awareness, counselling and support to senior citizens that are addicted to drug abuse.